1985
DOI: 10.1111/j.1467-2494.1985.tb00422.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity evaluation of nitroanilines and nitroaminophenols in Salmonella typhimurium

Abstract: Synopsis In our studies of structure-activity relationships, three nitroanilines and nine nitroaminophenols were tested for their ability to induce mutations in Salmonella typhimurium strains TA1535, TA100, TA1537, TA1538 and TA98. The compounds m-nitroaniline, 4-nitro-2-aminophenol, and 3-nitro-6-aminophenol were active in two or more of these strains. The compounds o-nitroaniline, 2-nitro-3-aminophenol, 3-nitro-4-aminophenol, 4-nitro-3-aminophenol, 3-nitro-2-aminophenol, 2-nitro-6-aminophenol, 2-nitro-4-amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 27 publications
0
3
0
2
Order By: Relevance
“…IACR classified benzidine and dyes metabolized to benzidine as category 1carcinogens (114). p-Phenylenediamine was reported to be non-mutagenic (126,127); but Shahin et al (128)(129)(130) reported it to be a weak mutagen. Chung et al (131) studied the mutagenicity of p-phenylenediamine and found it to be weakly mutagenic to Salmonella tester strain TA98 with metabolic activation.…”
Section: -Aminobiphenylmentioning
confidence: 99%
“…IACR classified benzidine and dyes metabolized to benzidine as category 1carcinogens (114). p-Phenylenediamine was reported to be non-mutagenic (126,127); but Shahin et al (128)(129)(130) reported it to be a weak mutagen. Chung et al (131) studied the mutagenicity of p-phenylenediamine and found it to be weakly mutagenic to Salmonella tester strain TA98 with metabolic activation.…”
Section: -Aminobiphenylmentioning
confidence: 99%
“…We tested the three unsubstituted NAs, 2NA, 3NA, and 4NA. Previous studies showed that 2NA is inactive in strain TA98 (Shahin, ; Shimizu and Yano, ; Blakey et al, ; Assmann et al, ) whereas 3NA and 4NA are positive, albeit weakly so (Shimizu and Yano, ; Chung et al, ; Assmann et al, ). We confirmed that 2NA is negative in TA98 and found that it was also negative in YG1024, with no increase in revertant yield up to the highest dose tested (1 μmol per plate); data not shown.…”
Section: Resultsmentioning
confidence: 96%
“…This compound can also be produced in the reduction of Methyl Orange, Orange II, Ponceau BS, and Ponceau S ( Table 2). p-Nitroaniline was first reported as very weakly mutagenic or non-mutagenic in the presence of S9 mix in S. Typhimurium strain TA98 (124). The mutagenicity of the compound was later confirmed in the test system of S. Typhimurium strain TA98 with or without S9 activation, but the results were negative for all other strains.…”
Section: Genotoxicity Of Metabolites Of Azo Dyesmentioning
confidence: 99%